The Influence Of Organizational Fairness, Organizational Culture and Job Satisfaction On Organizational Commitment - Tegar Hidayat, Tegar Hidayat; Subiyanto, Didik; Septyarini, Epsilandri (Journal of Business and Management Review, 2024)
Research Aims: This study aims to analyze the effect of organizational justice, organizational culture, and job satisfaction on organizational commitment among community members of Kampung Batik Giriloyo, Wukirsari, Bantul, DIY. Design/methodology/approach: This study is a quantitative research, by examining the cause-and-effect relationship of the variables Organizational Justice, Organizational Culture, Job Satisfaction, and Organizational Commitment, with 42 respondents.  Data was collected using a questionnaire using a Likert scale of 1 to 5, where 1 indicated "strongly disagree" and 5 indicated "strongly agree".  The collected data is processed with the SPSS program. Research Findings: 1) there is a positive and significant influence between organizational fairness and organizational commitment. (2) There is a positive and significant influence between organizational culture on organizational commitment. (3) There is a positive and significant influence between job satisfaction and organizational commitment. (4) There is a simultaneous positive and significant influence between organizational fairness, organizational culture, and job satisfaction on organizational commitment. Theoretical Contribution/Originality:  This integrated strategy includes a holistic approach that aims to simultaneously improve fairness, culture, and job satisfaction, which in turn will increase organizational commitment. By adopting this strategy, Paguyuban Kampung Batik Giriloyo can ensure long-term sustainability and success through the creation of an environment that supports and empowers each of its members. Keywords: Organizational Justice; organizational culture; job satisfaction; Organizational Commitment